Yayasan Bumiputera Sabah : The way forward / Azmi Abdul Majid, Luciana Eric and Victor Sani - Abdul Majid, Azmi; Eric, Luciana; Sani, Victor (2015)
The objective to conduct this study is to look into the ability of Yayasan Bumiputera Sabah organization structure to sustain business activities. Yayasan Bumiputera Sabah is a wholly own by the Sabah State Government with total contribution of RM100 million. However, throughout the years since its corporation in 1979, Yayasan Bumiputera Sabah has incurred huge accumulated losses which attributed mainly due to unperforming subsidiaries. The focus on this study is to understand the business structure, to investigate the financial position of Yayasan Bumiputera Sabah and to come up with strategic position. The findings show that there is a need to restructure the business organization to avoid further decline. This study only focuses on smaller group of respondents which are the top management of Yayasan Bumiputera Sabah. Further research may look into wider scope where the data sample should include all employees to obtain more accurate findings for Yayasan Bumiputera Sabah as a whole.